Studying the Formation of Biofilms on Supports with Different Polarity and Their Efficiency to Treat Wastewater - Stavroula Sfaelou; Hrissi K. Karapanagioti; John Vakros (Journal of Chemistry)
The main objective of this study was the evaluation of biofilm formation onto different supports and of biofilm efficiency to treat wastewater. Two different reactors were used, one with porous polyvinyl alcohol gel (PVA) biocarrier and another with a high-density polyethylene (PE) biocarrier. The reactor performance was evaluated and the biofilm formed was analyzed with potentiometric mass titrations. The biofilm formation was monitored with diffuse reflectance spectroscopy. The presence of the support did not alter the nature of the biofilm. However, the quantity of the biofilm formed was higher when polar surface groups were present on the support.